The Role of Christian Teachers based on Denpasar Local Wisdom in Developing Connectivist Learning in the Era of Digital Transformation - Wayan, Edwin; Yosafat (Harati: Jurnal Pendidikan Kristen, 2025)
This study aims to find out the role of Christian teachers in Denpasar in developing communicative learning in the era of digital transformation as well as the most significant factors that affect the role of teachers in the development of learning. The research method used was an explanatory survey, using a questionnaire distributed to 47 Christian teachers in Denpasar. The data obtained were analyzed using a regression model to evaluate the relationship between various teacher roles (as facilitators, knowledge curators, promoters of diverse perspectives, promoters of lifelong learning, promoters of collaboration, technology guides, and evaluators of learning connections) and the development of connective learning. The results of the study show that the role of Christian teachers in Denpasar in developing connective learning in the era of digital transformation has been going well and the role of teachers as promoters of collaboration and social learning is the most significant role in developing connective learning.